Intervensi Strategis Untuk Mengoptimalkan Manajemen Diri Lansia Dengan Hipertensi (Systematic Review) - Silvia Elki Putri; Etty Rekawati (FORIKES, 2020)
Culture in Indonesia influences all aspects of society, including health such as beliefs related to health management, health behavior and health care. One of the aggregates of concern regarding health in Indonesia is the elderly. The elderly are a vulnerable group who are at risk of experiencing health problems. Elderly with hypertension requires good management in health care. The objective of this review was to exploring interventions strategy to optimize the self-management of the elderly with hypertension. The design employed was a systematic review. The data was obtained from Wiley Online Library, Science Direct, Proquest, Research Gate, Springer Link, Google Scholar, and national journals from 2009-2019. The articles collected in this systematic review use the keywords